Treatment of osteoradionecrosis of the jaw with injectable platelet-rich fibrin (i-PRF): case series - Prisinoto, Nuryê Rezende; Oliveira, Guilherme José Pimentel Lopes de; Alves, Roberta de Oliveira; Cardoso, Sérgio Vitorino; Lima, Lívia Bonjardim; Soares, Priscilla Barbosa Ferreira (Brazilian Dental Science, 2024)
Objective: This study evaluated the use of autogenous blood concentrate (injectable platelet-rich fibrin) [i-PRF] for promoting soft tissue healing in osteoradionecrosis (ORN) lesions in patients who underwent head and neck radiotherapy. Material and Methods: This study included five ORN lesions in four patients who were treated with i-PRF (applied weekly for 4 weeks to the lesions). Soft tissue features were evaluated through clinical analysis at baseline and at 7, 15, 30, 60, and 90 days after the first session of i-PRF. Extension of the bone lesions was evaluated radiographically. Patient-centered related outcomes were evaluated using quality-of-life questionnaires at baseline and 90 days after the first treatment session. Quality of life data were analyzed using descriptive and frequency statistics and the Wilcoxon test. Results: Of the 5 treated lesions, 1 was completely closed and 3 remained open. The open lesions showed increased necrotic tissue exposure. No changes were observed in the radiographic appearance of the lesions. There was also no impact on the patient’s quality of life. Conclusion: The results suggest that the majority of ORN lesions remained stable after the application of i-PRF, with a slight improvement in the quality of the mucosa around the lesions. Furthermore, it was observed that i-PRF did not compromise the quality of life of patients during treatment. KEYWORDS Head and neck neoplasms; Osteoradionecrosis; Platelet-rich fibrin; Quality of life; Radiotherapy